2016
DOI: 10.1097/igc.0000000000000777
|View full text |Cite
|
Sign up to set email alerts
|

Omental Biopsy for Surgical Staging of Uterine Serous Carcinoma

Abstract: Omental involvement in USC upstages patients to stage IV disease and traditional risk factors fail to predict extrauterine disease. Although omental sampling does not influence disease progression or survival, a comprehensive intraoperative evaluation of the omentum is advised as most cases have grossly visible lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Additionally, only two of 8 patients had micrometastasis in this study (15). Therefore, the authors concluded that omentectomy as a part of comprehensive surgical staging for UPSC may not be necessary according to these two studies (14,15). However, this study represents that the rate of omental metastasis is consistent with the previous studies, as high as 21-25%, which suggests omentectomy or omental biopsy should be a part of the staging procedure for USC (10,11).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Additionally, only two of 8 patients had micrometastasis in this study (15). Therefore, the authors concluded that omentectomy as a part of comprehensive surgical staging for UPSC may not be necessary according to these two studies (14,15). However, this study represents that the rate of omental metastasis is consistent with the previous studies, as high as 21-25%, which suggests omentectomy or omental biopsy should be a part of the staging procedure for USC (10,11).…”
Section: Discussionsupporting
confidence: 68%
“…In this study, 66 out of 106 patients were undergone omentum biopsy (54; 82%) or omentectomy (12; 18%) and they found that only eight women (12%) had omental metastasis. Additionally, only two of 8 patients had micrometastasis in this study (15). Therefore, the authors concluded that omentectomy as a part of comprehensive surgical staging for UPSC may not be necessary according to these two studies (14,15).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The prevalence of omental metastasis in USC ranged from 10 to 17.4% [[12], [13], [14]]. Even in women with noninvasive serous carcinoma limited to the endometrium, the occurrence of omental metastases was as high as 5.1–9.8% (58/591) in clinical stage I nonendometrioid type endometrial cancer [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Third, it should be noted that the omentum is a common site of recurrence. Rita Luz reported that the most frequent sites of recurrence or progression in USC were the peritoneum (31%), followed by the omentum (27%), pelvis (18%), lungs (18%), and liver (14%) [13]. Thus, omentectomy may reduce recurrence.…”
Section: Discussionmentioning
confidence: 99%